2024
DOI: 10.1186/s12576-023-00897-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of the volume-sensitive/regulatory anion channel VSOR/VRAC. Part 1: from its discovery and phenotype characterization to the molecular entity identification

Yasunobu Okada

Abstract: The volume-sensitive outwardly rectifying or volume-regulated anion channel, VSOR/VRAC, which was discovered in 1988, is expressed in most vertebrate cell types and is essentially involved in cell volume regulation after swelling and in the induction of cell death. This series of review articles describes what is already known and what remains to be uncovered about the functional and molecular properties as well as the physiological and pathophysiological roles of VSOR/VRAC. This Part 1 review article describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 154 publications
0
6
0
Order By: Relevance
“…Electrophysiological and pharmacological evidence was provided for the VSOR/VRAC role in glutamate release from mouse astrocytes induced by hypoosmotic and ischemic stress [36]. Accordingly, DCPIB, which is a relatively most VSOR/VRAC-specific blocker among available anion channel blockers (see Reviews [1,12]), was shown to inhibit osmotic swelling-induced glutamate release from rat primary astrocytes [37] and human retinal glial Müller MIO-M1 cells [38] as well as the hypotonicity-induced release of aspartate, which is a non-metabolized analog of glutamate, from rat astrocytes [37,39]. However, DCPIB was unexpectedly found to inhibit not only glutamate release mediated by VSOR/ VRAC but also that mediated by connexin hemichannels as well as glutamate uptake via glutamate transporter GLT1 in rat glial cells [40].…”
Section: Vsor/vrac-mediated Glutamate Releasementioning
confidence: 99%
See 4 more Smart Citations
“…Electrophysiological and pharmacological evidence was provided for the VSOR/VRAC role in glutamate release from mouse astrocytes induced by hypoosmotic and ischemic stress [36]. Accordingly, DCPIB, which is a relatively most VSOR/VRAC-specific blocker among available anion channel blockers (see Reviews [1,12]), was shown to inhibit osmotic swelling-induced glutamate release from rat primary astrocytes [37] and human retinal glial Müller MIO-M1 cells [38] as well as the hypotonicity-induced release of aspartate, which is a non-metabolized analog of glutamate, from rat astrocytes [37,39]. However, DCPIB was unexpectedly found to inhibit not only glutamate release mediated by VSOR/ VRAC but also that mediated by connexin hemichannels as well as glutamate uptake via glutamate transporter GLT1 in rat glial cells [40].…”
Section: Vsor/vrac-mediated Glutamate Releasementioning
confidence: 99%
“…The homomeric LRRC8A channels reconstituted in liposomes were also found to be activated only in low Γ in solutions [31]. The channel activity was observed even in the absence of ATP and in the presence of a high concentration of free Mg 2+ on the intracellular side, in contrast to the phenotypical properties of native VSOR/VRAC existing in living cells (see Table 1 in Part 1 article [12]). Since the reduction in Γ in should increase the surface potential on the peripheral surface of highly charged domains of channel-forming proteins, physicochemical/electrostatic repulsion or attraction would take place between any pairs of closely adjacent charged domains or proteins.…”
Section: Swelling-independent Physicochemical Activation Of Vsor/vracmentioning
confidence: 99%
See 3 more Smart Citations